Estimated of Shelf Life Salem Fish Crackers (Scomber japonicus) with Polypropylene Plastic Packaging and Metalized Plastic in Poklahsar Mina Sejahtera, Tangerang - Permadi, Aef; Afifah, Rufnia Ayu; Latifa, Dian; Hidayah, Nur; Salampessy, Randi B.S.; Handoko, Yudi Prasetyo; Maulani, Aghitia (PELAGICUS, 2022)
Information on the shelf life of food products is one of the information that must be included on the label of food product packaging.  This study aims to obtain the estimated shelf life  of fried salem  fish cracker products  (Scomber japonicus)  packaged in polypropylene plastic  and metalized plastic.  Fried salem fish crackers (Scomber japonicus) are produced by Poklahsar "Mina Sejahtera" in Teluk Naga District, Tangerang Regency.  The estimated shelf life is carried out using the acceleration method with the critical moisture content model (Labuza model). The test results showed that the crackers had a water content of 2.67%. and a critical water content at the 9th hour with a water content of 6.53.%.   The permeability of polypropylene packaging and metalized plastic packaging is 0.0133 and 0.0032, respectively.  The results of the estimated shelf life of fried salem fish crackers (Scomber japonicus) packed with metalized plastic packaging with a thickness of 0.06 mm have a shelf life of 366 days and crackers packed with polypropylene packaging with a thickness of 0.08 mm have a shelf life of 130 days.  This shows that metalized plastic packaging has a better ability to maintain the durability of fried salem fish crackers.